MENINGKATAN KEMAMPUAN MENGENAL KONSEP BILANGAN DENGAN MENGGUNAKAN MEDIA BOLA ANGKA ANAK USIA 4 – 5 TAHUN DI TK AL-WASLIYAH SUNGAI MAJO KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Susilawati Susilawati; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Less improve the ability to know the concept of number, some children may not be able to count the numbers 1-10, some children may not be able to rekognize the concept of numbers 1-10, some children may not be able to mention the epitome numbers sequentially from the smallest to the largest, some children may not be able to mention the epitome numbers sequentially from the largest to the smallest, some children may not be able to mention the epitome 1-10 of random numbers. Therefore, it is necessary efforts to improve the ability to know the concept of numbers, namely through media activities the numeric balls. With the aim to determine the ability to recognize the concept of numbers at age 4-5 years, to find out how the application numbers ball media so as to enhance the chil’s ability to recognize the concept of number at age 4-5 years, to determine the increase in the ability to know of numbers by using ball media figures olds 4-5 years. Class action in two cycles. The tools used in data collecting observation sheet. The number of samples in this study were 15 children consisting of 8 man and 7 women. Results of two cycles increased, the increase occured, ie from before the action to cycle I at 34.12 %. Cycle I to CyCle II at 36.26% and the improvement of the prior cycle to cycle II of 82.76%.Keyword: Recognize The Concept Of Numbers